From reach to transformation: Leveraging the RBET Framework to secure women’s land and resource rights - Larson, Anne M.; Meinzen-Dick, Ruth S.; Trautman, S.; Atmadja, S.; Cronkleton, P.; Elias, Marlène; Gallagher, E. J.; Garner, E.; Morgan, M.; Paez-Valencia, A. M. (CIFOR-ICRAF, 2024)
The Reach, Benefit, Empower framework has been invaluable in guiding gender considerations in programming, ensuring that projects carefully consider their goals, and then move from ambition to implementation to evaluation. The framework makes it easier to see how projects claiming to “empower” women may only manage to “reach” them, such as through training, without actually verifying if the activities benefit or empower them. The addition of “Transform” to this framework (RBET for short) emphasizes the need for deeper structural or normative changes to create more equitable systems. In this brief we explore how to get the most out of the RBET framing in relation to securing women’s land and other resource rights.